2021
DOI: 10.1155/2021/5990417
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of Two-Dose Mumps-Containing Vaccine into Routine Immunization Schedule in Quzhou, China, Using Cox-Proportional Hazard Model

Abstract: Mumps is a vaccine-preventable disease caused by the mumps virus, but the incidence of mumps has increased among the children who were vaccinated with one-dose measles-mumps-rubella (MMR) in recent years. In this study, we analyzed the influence of different doses of mumps-containing vaccine (MuCV) against mumps using Cox-proportional hazard model. We collected 909 mumps cases of children who were born from 2006 to 2010 and vaccinated with different doses of MuCV in Quzhou during 2006-2018, which were all clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…A booster dose of MMR vaccine should be administered to high-risk groups such as students, and Anders Hviid et al showed that the ideal schedule for mumps vaccination should be determined to optimize vaccine control and suggested that the optimal age for the second dose remains to be determined ( 17 ). Regarding to the current immunization strategy in China, many studies advocate adjusting the timing and doses of MMR vaccination to reduce the future incidence of mumps in China, but there is insufficient theoretical support ( 15 , 18 ). The immunization schedules in China were adjusted after 2020 to one dose of MMR vaccine at 8 months of age and one dose at 18–24 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…A booster dose of MMR vaccine should be administered to high-risk groups such as students, and Anders Hviid et al showed that the ideal schedule for mumps vaccination should be determined to optimize vaccine control and suggested that the optimal age for the second dose remains to be determined ( 17 ). Regarding to the current immunization strategy in China, many studies advocate adjusting the timing and doses of MMR vaccination to reduce the future incidence of mumps in China, but there is insufficient theoretical support ( 15 , 18 ). The immunization schedules in China were adjusted after 2020 to one dose of MMR vaccine at 8 months of age and one dose at 18–24 months of age.…”
Section: Introductionmentioning
confidence: 99%
“…This is often the reason why the Cox proportional hazards model is used in most data studies. [10][11][12][13] In the proportional hazards regression model, unlike the Kaplan-Meier analysis, an assumption about the original form of the survival function is needed. In the Cox proportional hazards regression model, this function is assumed to be an exponential function, such as s(t)=exp(-kt).…”
Section: Cox Proportional Hazards Regression Modelmentioning
confidence: 99%
“…Moreover, Cox can include categorical variables (e.g., gender) and also numerical variables (e.g., age), whereas Kaplan-Meier curves and logrank tests can only include categorical variables [28,29]. Cox has a wider application since it extends survival analysis to simultaneously evaluate the effect of numerous risk factors on survival time [30]. Thus, we performed Cox based on IBM SPSS Statistics 26.…”
Section: Model Constructionmentioning
confidence: 99%